3D printing of fibre-reinforced cartilaginous templates for the regeneration of osteochondral defects. (1st September 2020) - Critchley, Susan; Sheehy, Eamon J.; Cunniffe, Gráinne; Diaz-Payno, Pedro; Carroll, Simon F.; Jeon, Oju; Alsberg, Eben; Brama, Pieter A.J.; Kelly, Daniel J.
Abstract: Successful osteochondral defect repair requires regenerating the subchondral bone whilst simultaneously promoting the development of an overlying layer of articular cartilage that is resistant to vascularization and endochondral ossification. During skeletal development articular cartilage also functions as a surface growth plate, which postnatally is replaced by a more spatially complex bone-cartilage interface. Motivated by this developmental process, the hypothesis of this study is that bi-phasic, fibre-reinforced cartilaginous templates can regenerate both the articular cartilage and subchondral bone within osteochondral defects created in caprine joints. To engineer mechanically competent implants, we first compared a range of 3D printed fibre networks (PCL, PLA and PLGA) for their capacity to mechanically reinforce alginate hydrogels whilst simultaneously supporting mesenchymal stem cell (MSC) chondrogenesis in vitro . These mechanically reinforced, MSC-laden alginate hydrogels were then used to engineer the endochondral bone forming phase of bi-phasic osteochondral constructs, with the overlying chondral phase consisting of cartilage tissue engineered using a co-culture of infrapatellar fat pad derived stem/stromal cells (FPSCs) and chondrocytes. Following chondrogenic priming and subcutaneous implantation in nude mice, these bi-phasic cartilaginous constructs were found to support the development of vascularised endochondral bone overlaid by phenotypically stable cartilage. These fibre-reinforced, bi-phasic cartilaginous templates were then evaluated in clinically relevant, large animal (caprine) model of osteochondral defect repair. Although the quality of repair was variable from animal-to-animal, in general more hyaline-like cartilage repair was observed after 6 months in animals treated with bi-phasic constructs compared to animals treated with commercial control scaffolds. This variability in the quality of repair points to the need for further improvements in the design of 3D bioprinted implants for joint regeneration. Statement of Significance: Successful osteochondral defect repair requires regenerating the subchondral bone whilst simultaneously promoting the development of an overlying layer of articular cartilage. In this study, we hypothesised that bi-phasic, fibre-reinforced cartilaginous templates could be leveraged to regenerate both the articular cartilage and subchondral bone within osteochondral defects. To this end we used 3D printed fibre networks to mechanically reinforce engineered transient cartilage, which also contained an overlying layer of phenotypically stable cartilage engineered using a co-culture of chondrocytes and stem cells. When chondrogenically primed and implanted into caprine osteochondral defects, these fibre-reinforced bi-phasic cartilaginous grafts were shown to spatially direct tissue development during joint repair. Such developmentally inspired tissue engineering strategies, enabled by advances in biofabrication and 3D printing, could form the basis of new classes of regenerative implants in orthopaedic medicine. Graphical abstract: Image, graphical abstract